Acesso aos medicamentos: uma proposta de análise conceitual e teórica - Santos, Paloma Oliveira dos (2022)
The objective of this dissertation was to analyze access to medicines from a conceptual and theoretical perspective. Thus, its development took place through conceptual analytical research, based on scientific literature. To map the concepts of access to medicines present in the literature, a scope review was carried out on studies published in Brazil in the last decade. It was evident that there is no consensus on the concept of access to medicines, pointing to the need to reflect on the subject, advancing in the elaboration of standards for the operationalization of the concept of access to medicines, aiming to make its scope and evaluation clearly feasible. Data from national and international literature on the conceptualization and measurement of access to medicines, dimensions, main determinants of access and also their barriers, supported the proposal of a model of analysis of access to medicines. Based on the proposed model, it is understood that access to medicines, at an individual and collective level, is influenced by user characteristics (health needs, beliefs and perceptions) and attributes of health services, inserted in a local and international context. , influenced by social, political, economic and marketing aspects. The results found contributed to understanding the complexity of access to medicines, concepts and dimensions, from a critical thinking focused on the need to rethink access to medicines, not only to the product, but within the provision of services aimed at the rational use of drugs. medicines. Thus, they are useful for the analysis and understanding of the phenomenon of access to medicines, allowing the development of appropriate strategies to improve access to medicines in the health services of the Unified Health System.